Role of crystallinity of non-fullerene acceptors in bulk heterojunctions1. Issue 18 (14th May 2015) - Sherman, Jes B.; Purushothaman, Balaji; Parkin, Sean R.; Kim, Chunki; Collins, Sam; Anthony, John; Nguyen, Thuc-Quyen; Chabinyc, Michael L.
<x xml:space="preserve">Abstract</x> The role of crystallinity of pentancene-based acceptors in BHJ solar cells is elucidated. The sandwich herringbone packing motif leads to higher performance than cofacial packing.